Development of bovine abomasum in prenatal period - do Nascimento, Gabriela Mansano [UNESP]; Perri, Silvia Helena Venturoli [UNESP]; de Carvalho, Roberto Gameiro [UNESP]; Monteiro, Cristina Maria Rodrigues [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2013)
For this purpose, samples of Nelore fetus abomasum (Bos taurus indicus) were classified into five groups: 1 - fetuses with 9 to 15 weeks (8 to 21 cm) of gestation, 2 - fetuses with 16 to 22 weeks (23 to 37 cm), 3 - fetuses at 23 to 29 weeks (40 to 58 cm) 4 - fetuses with 30 to 36 weeks (61 to 77 cm) and 5 - fetuses with 37 to 43 weeks (79 to 88 cm). Histologic sections were stained with Hematoxylin and eosin, picrosirius and Mallory's trichrome methods and examined under light microscopy. In fetus with 11 cm of length showed deep mucosa, wide folds and villi lined by single cylindrical epithelium, lamina propria, submucosa, muscular sublayers and serosa. Fetus with 13.5 cm, villi were evident and muscular layer of the mucosa was formed. At 16.5 cm, could be seen an increase in mucosa glands size and number. In fetus of 26 cm, showed gastric mucous glands at great number and ramifications. At 29 cm large folds, were observed. At 37 cm, showed glandular epithelium, muscular layer of the mucosa and muscular layer well development. Fetus with 42 cm, showed deep glands with corresponding mucous cells surrounding by thin lamina propria. It was concluded that the histomorphometric values of muscular layer and total abomasum wall were increased for all groups except for groups 4 and 5 which there was a decline of values, without presenting a significant difference and there was no continuous pattern of growth for other components of abomasum wall.
Desenvolvimento do abomaso de bovinos no período pré-natal
Keywords: Abomasum; Fetuses; Morphology; Ruminants